Application of Dermobacter in The Treatment of Purulent Atheroma in The Facial Area - Ashurov Sanjarbek Saydullo ugli (Scholars Digest Publishing, 2023)
The problem of purulent infections in the field of maxillofacial surgery has been and remains topical due to the increasing number of patients with inflammatory processes in the maxillofacial region, increasing number of severe generalized infections. Despite the widespread introduction into clinical practice of such methods of treatment as local and general surgical care, the use of antibacterial drugs and chemotherapeutic agents, detoxification and corrective therapy, the treatment of joint diseases, modern physiotherapeutic agents, inflammatory diseases of the maxillofacial region, continues.
Keywords: facial area, purulent atheroma, dermobacteria.